2000
DOI: 10.1152/physiologyonline.2000.15.5.213
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Nerve Interactions

Abstract: Mutual associations between nerves and mast cells have been observed in normal conditions and in pathological ones such as human irritable bowel syndrome, atopic dermatitis, interstitial cystitis, and more. Here we review the recent literature in this field, putting emphasis on the enteric, skin, and urinary systems, and the pathophysiological implications of this interaction in them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 15 publications
5
77
0
2
Order By: Relevance
“…It has also been reported that MCs are localized near the SP-positive neurons where SP promotes the release of histamine [64]. Ghrelin-positive MCs localization near the autonomic nerves in the rat stomach wall correlates with results detecting MCs near the peptidergic nerves in other organs and species [23][24][25]. According to earlier studies, the neuropeptides can influence the secretion of MC cytokines which exert their modulatory effect in neurogenic inflammation [66][67][68].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…It has also been reported that MCs are localized near the SP-positive neurons where SP promotes the release of histamine [64]. Ghrelin-positive MCs localization near the autonomic nerves in the rat stomach wall correlates with results detecting MCs near the peptidergic nerves in other organs and species [23][24][25]. According to earlier studies, the neuropeptides can influence the secretion of MC cytokines which exert their modulatory effect in neurogenic inflammation [66][67][68].…”
Section: Resultssupporting
confidence: 61%
“…MC secreting histamine, substance P (SP), vasoactive intestinal polypeptide (VIP) and other factors are mobile that make contact with peptidergic nerve endings (secreting also SP, VIP, etc.) in tissues and maintain in this way tissue homeostasis and participating in arising inflammation [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…M ast cells in the CNS are located on the brain side of the blood-brain barrier (BBB). Mast cells can potentially mediate neurotransmission, neurite outgrowth, and neuronal survival in the brain (1,2). Mast cells are associated with various physiological and pathophysiological conditions, such as the estrus cycle, behavior, vascular headaches, and multiple sclerosis (MS) (3).…”
mentioning
confidence: 99%
“…16 -21 Afferent nerves express specific receptors for neuropeptides, 22 prostaglandins, 23 histamine, 24 proteases, 25 neurotrophins, 26 and cytokines, 27,28 and mast cells can also respond to many of these products. 1,2,15,29,30 Moreover, certain adhesion molecules, such as N-cadherin 31 and spermatogenic Ig superfamily/ synaptic cell adhesion molecule, 32 have been shown to be important in mediating interactions between nerves and mast cells.…”
mentioning
confidence: 99%